Being transdisciplinary theologians in and beyond apocalyptic environments - Loubser, Gys M. (HTS teologiese studies, 2016)
This article offers a description of transdisciplinary facilitation that is suitable for theologians and ministers. The reflective aspect of transdisciplinary facilitation is illustrated through an engagement with transdisciplinary research on environmentalism and ecotheology. This article also suggests that Ernst Conradie could be appreciated, drawn on and critiqued as a transdisciplinary theologian and not a contextual theologian.